Hubungan Antara Kecerdasan Emosional dengan Organizational Citizenship Behaviour (OCB) Pada Karyawan SPBU Sijunjung: Hubungan Antara Kecerdasan Emosional dengan Organizational Citizenship Behaviour (OCB) Pada Karyawan SPBU Sijunjung - irdam, irdam; Belly Natura; Nur Aulia Dina (Sumatera Scientist, 2025)
This study aims to look at the relationship between emotional intelligence and organizational citizenship behavior. The independent variable in this study is emotional intelligence and the dependent variable is organizational citizenship behavior. The measuring instrument used in this research is the scale of emotional intelligence and the scale of organizational citizenship behavior. The sampling technique used in this study was purposive sampling with a total sample size of 41 people. Validity and reliability test using Alpha Cronbach technique. The results of the validity coefficient on the emotional intelligence scale ranged from 0.721 to 0.924, while the reliability coefficient was 0.972. The results of the validity coefficient on the scale of organizational citizenship behavior ranged from 0.715 to 0.933, while the reliability coefficient was 0.972. The results of data analysis show that the correlation coefficient is 0.967 with a significant level of p = 0.000. This means that there is a significant relationship with a positive direction between emotional intelligence and organizational citizenship behavior (OCB) on Sijunjung SPBU employees.So it can be interpreted that the hypothesis in this study is accepted. The effective contribution of the emotional intelligence variable to organizational citizenship behavior (OCB) of adolescents is as much as 93,%.